Kajian Perkembangan Perumahan di Kecamatan Deli Tua - Sembiring, Rahmad Dian; Pinem , Dessy Eresina (Jurnal Sains dan Teknologi ISTP, 2024)
The development of settlements can cause land shortages through several mechanisms of population growth and urbanization. The increase in population in an area requires more land for housing and supporting facilities, such as schools, hospitals, and shopping centers. This can lead to an increase in demand for land that exceeds the availability of existing land. The rapid urbanization process often leads to the expansion of cities into suburban or rural areas. This results in the conversion of agricultural land and open space into settlements, which reduces the amount of land available for other uses. However, of course, the development of settlements must still pay attention to land capabilities. This study aims to find directions for the development of residential land in the future by considering land capabilities in Deli Tua District. This study uses a geometric projection method, projection of the number of facility needs using SNI 03-1733-2004 on Procedures for Planning Urban Housing Environments and mapping land capabilities based on Permen PU No. 20 of 2007. The findings of this study are that Deli Tua District will experience a shortage of land for housing development for the next 20 years so that the following alternatives must be carried out, namely Vertical housing development, Housing development outside Deli Tua District and using land with low development capability (SKL) meaning that more technology must be used so that the use of this land is safe for housing and settlement development.